INTERDISCIPLINARY BEDSIDE ROUNDS AND ITS IMPACT ON HOSPITAL LENGTH OF STAY - Yustama, Ida Bagus Yudistira Nugraha (Jurnal Manajemen dan Administrasi Rumah Sakit Indonesia (MARSI), 2025)
Introduction: Health-care services has developed towards patient-centered care (PCC). Currently, cases of the prolonged length of stay in hospital arises due to the lack of holistic approach. This study aims to analyze the role of IBR (interdisciplinary bedside rounds) implementation and its impact on hospital LOS (length of stay).Methods: This scoping review was adapting the PICOS framework and reporting guidelines by Prisma. Google scholar, PubMed, Cochrane, and Embase were systematically searched for key IBR words and concepts from 2019. Eligibility of the study uses inclusion and exclusion criteria. Seven articles met inclusion criteria and underwent data abstraction.Results: IBR implementation was able to decrease LOS as it empowers communication between interprofessional teams and patients/families during rounds and improves patient outcomes. However, it was still debated as IBR’s implementatios were found innefective due to multiple confounding factors including elderly patient with acute illness combined with comorbidities of dementia, delirium, and gap of language barrier as the external factors, and the team readiness as the internal factors.Discussion: This scoping review highlights IBR’s impact on reducing the LOS and the need for further studies which considers the confounding factors. Keywords: Interdisciplinary bedside rounds, length of stay, scoping review